The relationship between sleep quality and psychological resilience of college students: the examination of insomnia as a mediator and attachment as a moderator - Zhang, Yi; Li, Juanjuan; Dong, Jianyu; Shi, Lingling; Zhang, Ning (Frontiers in Psychology, 2025)
BackgroundSleep quality received widespread attention as a significant factor influencing psychological resilience. Existing research has inadequately addressed the relationship and the mechanism between sleep quality and the psychological resilience of college students.ObjectiveThis study aims to explore the relationship between sleep quality and psychological resilience among college students, while examining how insomnia and attachment security mediate this association. This study may provide advice for promoting the sleep quality and psychological resilience of college students.MethodsA total of 585 college students from multiple universities in Beijing were selected through convenience sampling via questionnaire survey. Data was collected using students’ self reported sleep quality with the Pittsburgh Sleep Quality Index (PSQI), insomnia symptoms with the Insomnia Severity Index (ISI), attachment security with Adult Attachment Scale (AAS) and psychological resilience with Psychological Resilience Scale (PSR). Robust linear regression model and structural equation model were employed to analyze the relationship between sleep quality and psychological resilience among college students.ResultsUniversity students in Beijing show a certain degree of sleep problems (mean PSQI = 8.27, SD = 3.56), with 43.59% having experienced insomnia. Their psychological resilience is relatively good (mean = 3.48, SD = 1.81). There is a positive correlation between sleep quality and insomnia index among college students (β = 1.36, p < 0.001); poorer sleep quality is associated with lower psychological resilience (β = −0.02, p < 0.05), higher insomnia index is associated with lower resilience (β = −0.01, p < 0.1), and students with insecure attachment exhibit lower psychological resilience compared to those with secure attachment (β = −0.50, p < 0.001). Of the total effect of sleep quality on psychological resilience, 39.24% is mediated through insomnia, while the remaining 60.76% is a direct effect. Adult secure attachment can effectively moderate the sleep–insomnia pathway. This research may help to understand the relationship among sleep quality, attachment, and psychological resilience.